Study of Sonocatalytic Activity ZnO-WO3 Composite on Degradation Phenol in Aqueous Solution (Universitas Negeri Semarang, 2022)
Sonocatalysis was used to study phenol degradation using a ZnO/WO3 composite. The degradation was assisted by ultrasonic waves at 40 KHz and conducted using the sonocatalysis technique. The degradation percentage was calculated using data from the UV-Vis spectrophotometer. The composite characterization results showed that the samples containing WO3, ZnO and also contained a new structure ZnWO4. The morphological length and width of the composites were revealed by SEM examination. Furthermore, heterogeneous particle sizes were discovered. The surface area of composite was bigger than before combined. The optimum condition in degradation of phenol by ZnO-WO3 composite are 0,4 g of catalyst at 30 ppm of phenol, 7 min reaction time with the greatest phenol degradation at 92,5%. The catalyst can be reused 5 times to degrade phenol at 85%. The composite catalyst and assisted with ultrasonic as the sonocatalytic technique are one of the most environmentally and cost effective.